2019
DOI: 10.1016/j.molcel.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pre-mRNA Cleavage Prevents Replication-Stress-Associated Genome Instability

Abstract: Summary Cellular mechanisms that safeguard genome integrity are often subverted in cancer. To identify cancer-related genome caretakers, we employed a convergent multi-screening strategy coupled to quantitative image-based cytometry and ranked candidate genes according to multivariate readouts reflecting viability, proliferative capacity, replisome integrity, and DNA damage signaling. This unveiled regulators of replication stress resilience, including components of the pre-mRNA cleavage and polyade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 66 publications
2
75
0
Order By: Relevance
“…RNase H2 is able to remove RNA-DNA hybrids in R-loops as well as perform RER (Cerritelli and Crouch, 2009). MMS induces DNA damage and replication stress, both of which can lead to the stabilization and generation of R-loops (Hamperl et al, 2017;Svikovic et al, 2018;Teloni et al, 2018) (Figure 2), which likely contribute to the MMS sensitivity of rnh1 rnh201 cells. R-loop stabilization in sen1-1 mutants is also responsible for lethality in rnh1 rnh201 double mutants (Costantino and Koshland, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNase H2 is able to remove RNA-DNA hybrids in R-loops as well as perform RER (Cerritelli and Crouch, 2009). MMS induces DNA damage and replication stress, both of which can lead to the stabilization and generation of R-loops (Hamperl et al, 2017;Svikovic et al, 2018;Teloni et al, 2018) (Figure 2), which likely contribute to the MMS sensitivity of rnh1 rnh201 cells. R-loop stabilization in sen1-1 mutants is also responsible for lethality in rnh1 rnh201 double mutants (Costantino and Koshland, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, both the S-and G2-alleles of RNase H1 were able to support growth in sen1-1 cells ( Figure 5), suggesting that when R-loops accumulate, RNase H1 can act irrespective of cell cycle stage. This scenario was mirrored in the presence of MMS, which can induce DNA damage and replication stress, both of which can allow R-loops to accumulate and become stabilized (Hamperl et al, 2017;Teloni et al, 2018). Indeed, both the Sand G2 -expressed alleles of RNase H1 could support the growth of rnh201 cells in the presence of MMS.…”
Section: Discussionmentioning
confidence: 99%
“…To exacerbate the formation of secondary structures during DNA replication, we evoked conditions of enhanced replicative helicase/polymerase uncoupling by treating RPE-1 cells for 90 min or 2 h with hydroxyurea (HU), which inhibits ribonucleotide reductase and, thereby, depletes the nucleotide pool, and the ataxia telangiectasia and Rad3-related protein (ATR) inhibitor VE-821 (ATRi). In these conditions, using quantitative image-based cytometry (QIBC) (Toledo et al, 2013;Teloni et al, 2019), we observed a reduction in native ssDNA upon depletion of DDX11, specifically in S-phase cells (Fig 5A and C).…”
Section: Ddx11 Promotes the Generation Of Ssdnamentioning
confidence: 92%
“…Disruption of WDR33 can lead to slowed DNA replication forks (49), which could potentially explain why its disruption protects against topoisomerase inhibitors that block DNA unwinding.…”
Section: Etoposide Resistance Is Modulated By Levels Of Wdr33mentioning
confidence: 99%